Implementation and Implications of Regional Government Information System (SIPD) on Expenditure Administration - David P. E. Saerang; Hendrik Gamaliel; Florensia Bernika (Accounting and Finance Studies, 2023)
This study aims to determine the implementation the Regional Government Information System (SIPD) in the implementation of expenditure administration and the implications faced in the implementation of the local government information system. This research uses a qualitative method with a case study approach. Data collection was carried out by means of in-depth interviews and documentation studies. The results showed that the Local Government Information System Application at BPKAD Manado City is a computer application program that has been integrated and synchronized by one data at the Central Government, namely SIPD, one of the efforts in order to meet information needs quickly, precisely, completely, accurately and integrated. In addition, this can help the Central Government in controlling the financial activities of the Regional Government, but there are still several obstacles and obstacles that need to be addressed in order to optimally implement SIPD. In addition, the SIPD implementation policy in Manado City is in accordance with Peraturan Menteri Dalam Negeri No. 70 of 2019. From the aspects of resources, the character of the implementing agents, and the attitudes of the implementers, it still describes implementers who have minimal knowledge of SIPD and communication between implementing agents has not been maximized. The positive thing in the implementation of SIPD in Manado City is the existence of conditions conducive to the external environment (economic, social, and political environment). The implementation of SIPD creates practical constraints, such as network constraints that interfere with the data verification process and difficulties in communicating with implementing agents. Efforts to overcome obstacles are to conduct regular training programs for SIPD implementing employees with training materials that have been packaged easily so that the attitude of the SIPD implementing agents themselves can accept the new policy.